Introduction to hospitality management - Reynolds, Dennis E.; Barrows, Clayton W.; Rahman, Imran (Wiley, 2021)
If any phrase best characterizes the hospitality and tourism industry today it would be "constantly changing." The COVID-19 pandemic represents the most significant recent change, one that no one could have predicted. Unfortunately, the pandemic affected the hospitality industry more severely than most others. In addition, worldwide recessionary economic conditions, globalization, and an industry-wide focus on sustainability and corporate responsibility are among the other forces converging and resulting in widespread change. The result is an industry that requires future leaders in hospitality and tourism to be well versed in past, current, and emerging management practices. To this end, Introduction to Hospitality Management offers a holistic overview of our dynamic industry that includes historical perspectives but with a strong emphasis on new trends and best practices in a wide range of segments. Building on traditions established in past editions Introduction to Management in the Hospitality Industry, our goal is to provide educators and students with the most up-to-date content with the hope that the next generation of global hospitality leaders will be fully prepared to meet the challenges of this dynamic industry"--